2018
DOI: 10.3847/2041-8213/aab434
|View full text |Cite|
|
Sign up to set email alerts
|

Discovery of New Coronal Lines at 2.843 and 2.853 μm

Abstract: Two new emission features were observed during the 2017 August 21 total solar eclipse by a novel spectrometer, the Airborne Infrared Spectrometer (AIR-Spec), flown at 14.3 km altitude aboard the NCAR Gulfstream-V aircraft. We derive wavelengths in air of 2.8427 ± 0.00009 μm and 2.8529 ± 0.00008 μm. One of these lines belongs to the transition in Ar-like Fe ix. This appears to be the first detection of this transition from any source. Minimizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 34 publications
2
28
0
Order By: Relevance
“…Note-Wavelength estimates and standard errors are reported for each of the four coronal slit positions. The Fe IX line was only seen in position 3 (Samra et al 2018;Samra et al 2019).…”
Section: Dark Subtractionmentioning
confidence: 96%
See 1 more Smart Citation
“…Note-Wavelength estimates and standard errors are reported for each of the four coronal slit positions. The Fe IX line was only seen in position 3 (Samra et al 2018;Samra et al 2019).…”
Section: Dark Subtractionmentioning
confidence: 96%
“…Prior measurement campaigns have confirmed the existence of Si X at 1.431 µm (Penn & Kuhn 1994;Kuhn et al 1996), S XI at 1.921 µm (Olsen et al 1971;Kastner 1993), Mg VIII at 3.028 µm (Münch et al 1967;Olsen et al 1971), and Si IX at 3.935 µm (Kuhn et al 1999;Judge et al 2002). AIR-Spec made the first detection of Fe IX at 2.853 µm (Samra et al 2018). Through coordinated observations with the Extreme Ultraviolet Imaging Spectrometer (EIS, Culhane et al 2007), the AIR-Spec measurements provided insight into line excitation processes and coronal temperature and density Madsen et al (2019).…”
Section: The August 21 2017 Eclipse Datamentioning
confidence: 97%
“…The authors found that the architecture and modernity of the instruments were still inadequate to detect coronal lines from low-altitude sites due to various sensitivities such as atmospheric absorption and background. The Airborne Infrared Spectrometer (AIR-Spec) was constructed with the goal of studying several magnetically sensitive coronal lines, assessing their validity to pursue as future spectro-polarimetric observations (Samra et al 2018). The combination of the moderate-resolution FTS and AIR-Spec spectra therefore clearly revealed for the first time the effects of telluric extinction on the IR coronal emission lines.…”
Section: Introductionmentioning
confidence: 99%
“…Mg VIII ∼3028nm, are detectable in ground observations is still debatable. Theoretical intensity calculations and older observational runs are reserved (Münch 1966;Olsen et al 1971;Judge 1998), but a definitive ruling has not been reached, as discussed by Judge et al (2001) and Samra et al (2018). For this reason, we limited our coronal line selection to encompass only the more reliable Fe XIII, Si X, and Si IX ions.…”
Section: Introductionmentioning
confidence: 99%
“…AIR-Spec was commissioned during the 2017 eclipse, when it observed five emission lines between 1.4 and 4 µm (Table 1). The 2.853 µm Fe IX line was detected for the first time (Samra et al 2018), and coordinated observations with the Hinode Extreme Ultraviolet Imaging Spectrometer (EIS, Culhane et al 2007) were used to characterize plasma temperature and density (Madsen et al 2019).…”
mentioning
confidence: 99%